Capsaicin: preclinical and clinical studies - Qureshi, Absar A.; Qureshi, Azfar A.; Omer, Shaista; Sanghai, Dhirendra B.; Setty, S. R.; Bhajipale, N. S. (Plant Archives, 2008)
Drugs obtained from plant sources occupy important position in different pharmacopoeias. Many of the life saving drugs in the present day allopathic system are obtained from plant origin only. Extensive scientific research on capsaicin, a natural compound, pungent principle, present in the fruits of plant Capsicum anum, has been performed. In preclinical studies capsaicin shows lipid lowering by stimulating its metabolism, gastroprotection against aspirin and ethanol induced ulcers. Capsaicin in rodents shows anticancer activity against NKK induced lung and liver cancer. It also exhibits antidiabetic, antimicrobial, anti-inflammatory and antioxidant properties in rodents. In clinical studies Capsaicin shows gastroprotection in healthy volunteers. In double blind studies capsaicin proved to be useful in skin disorders against prutitic psoriasis and prurigo nodularis with randomized double blind studies. It also exhibits good analgesic activity against post-therapeutic neuralgia, osteo-arthritis, rheumatoid arthritis and diabetic neuropathy. Capsaicin is fairly safe with oral dose 0.5-1.0 mg/kg.
Keywords: capsaicin; Capsicum anum; clinical studies; preclinical

Phytochemical constituents and pharmacological activities of calotropis procera - Qureshi, Absar A.; Qureshi, Azfar A.; Omer, Shaista; Sanghai, Dhirendra B.; Setty, S. R.; Bhajipale, N. S. (Plant Archives, 2008)
In spite of many synthetic compounds, the most efficient drugs have their origin directly or indirectly related with the plant kingdom. Many of the plant extracts have proven to posses important pharmacological actions depending upon the chemical constituents present. Calotropis procera, plant generally considered as a poisonous whereas widely used in the traditional medicinal system like Ayurveda and Unani. This plant has been reported to poses alkaloids, glycosides, flavonoids, triterpines etc in different parts and exhibit various pharmacological activities like anti-fertility, wound healing, antimalerial, antidiarrhoeal, anti-inflammatory etc. This review highlights some of the phytochemical and pharmacological aspects of Calotropis procera.
Keywords: calactin; calotoxin; Calotropis procera; pharmacological activities; phytochemical constituents; procesterol